Antimalarial Drugs-Induced Hepatic Injury in Rats and the Protective Role of Carnosine - Akram Jamshidzadeh, Reza Heidari, Farzaneh Abazari, Maral Ramezani, Forouzan Khodaei, Mohammad Mehdi Ommati, Maryam Ayarzadeh, Roya Firuzi, Arastoo Saeedi, Negar Azarpira, Asma Najibi (Tabriz University of Medical Sciences, 2016)
Background: Chloroquine and amodiaquine are used in the prophylaxis and treatment of malaria. However, hepatic injury is associated with malaria drug therapy. On the other hand, there is no promising hepatoprotective agent for prophylaxis or treatment of antimalarial drugs‑induced liver injury. Carnosine is a naturally occurring peptide with pleiotropic protective properties in different tissues. This investigation aimed to evaluate the effect of carnosine administration in antimalarial drugs-induced hepatic injury in rats. Methods: Animals were treated with amodiaquine (180 mg/kg, oral) or chloroquine (970 mg/kg, oral). Carnosine (250, 500 and 1000 mg/kg, i.p) was administered as the hepatoprotective agent against antimalarial drugs liver injury. Results: Liver injury was manifested biochemically by a significant increase in serum level of ALT, LDH, and AST. In addition, hepatic tissue from antimalarial drugs‐treated rats showed a significant increase in reactive oxygen species (ROS), lipid peroxidation and protein carbonylation along with a decrease in hepatic glutathione reservoirs and total antioxidant capacity. Moreover, the liver histopathologic evaluation revealed significant congestion, inflammation, and necrosis in amodiaquine and/or chloroquine-treated animals. Carnosine administration significantly alleviated antimalarial drugs-induced pathologic changes in serum biochemistry and liver tissue. Conclusion: Our data suggest that carnosine possesses protective properties against amodiaquine and/or chloroquine‑induced liver injury possibly through mitigation of drug-induced oxidative stress and its consequent events.